"Transverse Action" – A model benchmark exercise for numerical analysis of the Callovo-Oxfordian claystone hydromechanical response to excavation operations. (May 2017) - Seyedi, Darius M.; Armand, Gilles; Noiret, Aurélien
Abstract: The Callovo-Oxfordian claystone (COx) is considered as a potential geological formation to host an industrial radioactive waste repository in France. A detailed understanding of the thermo-hydro-mechanical (THM) behavior of the COx is a key issue for design of different repository structures and the safety calculations of the project. More particularly, numerical modeling of induced fracture networks around drifts excavated at the main level of the Andra's Meuse/Haut-Marne Underground Research Laboratory (M/HM URL) and short and long term behavior of the COx around these drifts are of great interest. Several constitutive models have been developed/used in the framework of the R&D and simulation programs of Andra. A model benchmark exercise has been launched since 2012 to provide an overall view of the developed models regarding the in situ observations. In this view, two series of test cases, respectively at material point scale and at drift excavation scale are defined. Different kinds of constitutive models based on the elasto-visco-plasticity concept, continuum damage mechanics, the rigid block spring method and two-scale computational homogenized model (CHM) are used within this exercise. The obtained results show that accounting for material anisotropy and strain localization treatment techniques can improve the obtained results when elasto-visco-plastic models are used. Damage mechanics based approaches and methods accounting for discontinuities through discrete elements provide also interesting insights especially when fracturing processes must be modeled. However, more efforts are necessary to improve the robustness of these kinds of approaches in the complex context of COx response to excavation works.